2015
DOI: 10.1097/mph.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid for the Treatment of Children With Refractory Central Giant Cell Granuloma

Abstract: There are no approved medical therapies for the treatment of pediatric central giant cell granuloma (CGCG), a benign but potentially aggressive tumor of the jaw. Zoledronic acid (ZA), a third-generation bisphosphonate, has been used in CGCG occurring in adults. We describe 4 patients with CGCG treated with ZA, 3 of whom achieved resolution of disease up to 4 years of follow-up. Our experience suggests that ZA may be considered as treatment for pediatric CGCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Currently, GCLJ are treated by conservative surgery. Besides surgery, GCLJ are occasionally treated with corticosteroids [85], calcitonin [86,87], bisphosphonates [88], or interferon alpha [89] in addition to denosumab (a RANKL inhibitor) [90], with variable responses [86,91]. Notably, RANKL is expressed in the GCLJ mononuclear cells [92] and its expression by GCLJ mononuclear 'stromal' cells influences the differentiation of monocyte/macrophage precursors into osteoclast-like giant cells [75].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Currently, GCLJ are treated by conservative surgery. Besides surgery, GCLJ are occasionally treated with corticosteroids [85], calcitonin [86,87], bisphosphonates [88], or interferon alpha [89] in addition to denosumab (a RANKL inhibitor) [90], with variable responses [86,91]. Notably, RANKL is expressed in the GCLJ mononuclear cells [92] and its expression by GCLJ mononuclear 'stromal' cells influences the differentiation of monocyte/macrophage precursors into osteoclast-like giant cells [75].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Its aetiology is still uncertain making it difficult to treat. Several therapies have been proposed in the literature, from corticosteroids, calcitonin, interferons and bisphosphonates (7), to more radical procedures such as surgical enucleation with curettage, and resection (8). It is usually classified as a circumscribed, non-cortical, multilocular and radiolucent lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological agents, including calcitonin [9, 10], IFN-α [8], and denosumab [11], are promising alternatives to surgical management. Pharmacological agents have the potential to decrease the recurrence rate, minimizing the morbidity associated with surgery, and even prevent the need for surgical intervention [9, 12, 13]. A double-blind clinical study reported that calcitonin significantly reduced the recurrence rate of central giant cell granuloma after curettage.…”
Section: Discussionmentioning
confidence: 99%